Recent progress in metal–organic polymers as promising electrodes for lithium/sodium rechargeable batteries - Wu, Zhenzhen (2020)
Metal organic polymers (MOPs), including metal coordination polymers (CPs, one-dimensional), metal–organic frameworks (MOFs, two-/three-dimensional), Prussian blue (PB) and Prussian blue analogues (PBAs), have recently emerged as promising electrochemically active materials for energy storage and conversion systems. Due to the tunability of their composition and the structural versatility, diverse electrochemical behaviors for multi-electron reactions, fast-ion diffusion, and small volume change of electrodes could be achieved upon charging and discharging. Because of these superiorities, MOPs are considered as effective substitutes for future advanced energy storage systems. Here, we summarize the recent progress in pristine MOPs as electrode candidates for rechargeable lithium and sodium ion batteries. The working mechanisms and strategies for enhancing the electrochemical performance in related advanced electrochemical energy storage (EES) applications are also highlighted in this review.